β-Cyclodextrin and Oligoarginine Peptide-Based Dendrimer-Entrapped Gold Nanoparticles for Improving Drug Delivery to the Inner Ear - Luo, Jia; Lin, XueXin; Li, LiLing; Tan, JingQian; Li, Peng (Frontiers in Bioengineering and Biotechnology, 2022)
We describe a safe and highly effective nano-carrier based on β-cyclodextrin(β-CD) and oligoarginine peptide (Arg8) modified dendrimer-entrapped gold nanoparticles (Au@CD-PAMAM-Arg8) at 5nm in diameter for improved drugs delivery, such as dexamethasone (Dex), to inner ear. We use streptomycin (SM) ototoxicity model to verify the efficiency and potential of drug carriers for loading drugs in vivo. The material properties and distribution in vivo and biological potential of the Au@CD-PAMAM-Arg8 was assessed by various methods. Flow cytometry analysis of HEIOC1 cells treated with drug delivery carrier Au@CD-PAMAM-Arg8 and Au @CD-PAMAM at different time intervals indicated that cell uptake efficiency of drug delivery carrier Au@CD-PAMAM-Arg8 was higher than Au @CD-PAMAM and the duration of administration was longer. Confocal and immunostaining targeted with Dex results revealed that Au@CD-PAMAM-Arg8/Dex was mainly distributed in hair cells, spiral ganglion, lateral wall and nerve fibers and had a stronger protective effect on their morphological integrity after SM treatment than Dex administration alone. In vivo tracers test showed that the effect of tympanic injection was significantly better than posterior ear injection, muscle injection and tail vein injection, while clinical retro-auricular injection cannot increase the efficiency of drugs into the ear. Electrocochleography (ECochG) In Vivo results demonstrated that Au@CD-PAMAM-Arg8/Dex significantly improved hearing in C57/BL6 mice after SM exposure. Those work indicated that Au@CD-PAMAM-Arg8 may be an important drug carrier in dealing with inner ear diseases and the clinical application of Au@CD-PAMAM-Arg8 in inner ear disease is promising.